Step towards Formulating a Maximum Surgical Blood Ordering Schedule in Obstetrics and Gynecology: An Audit of Blood Utilization Practices in a Teaching Hospital in Nepal - Aryal, Shreyashi; Shrestha, Deepak; Bharadwaj, Brijbala (Journal of Lumbini Medical College, 2017)
Introduction: Blood transfusion is an essential part of perioperative care in surgeries in obstetrics and gynecology. A tendency of over ordering of blood imposes additional workload to the blood bank and extra cost to the laboratory and patients. Maximum surgical blood ordering schedule (MSBOS) is a guide which helps in the decision of ordering and transfusing blood which reduces blood wastage. This study was done with the aim of evaluating the blood ordering and utilization patterns in obstetric and gynecologic surgeries and formulation of MSBOS for these procedures for the institute. Methods: This is a cross-sectional, hospital based study conducted for the duration of three months. All patients undergoing major and minor surgeries at the department were included. Crossmatch to transfusion ratio (C/T), transfusion probability (%T), transfusion index (TI) and MSBOS were calculated for each procedure. Results: Total 309 surgeries were performed in the department during the study period of three months. Most common surgery was emergency cesarean section (n=164, 53.1%) followed by abdominal hysterectomy (n=43, 13.9%). Utilization of cross matched blood was 22.51%. Overall transfusion rate for all surgeries was 3.88%. Overall C/T ratio, %T, and TI were 4.44, 9.83 and 0.27 respectively which elicited indiscriminate ordering of blood. Conclusion: Over ordering and under utilization of blood were seen in this audit. Blood ordering patterns need to change in order to minimize over ordering of blood which may prevent abuse of the system. MSBOS maybe an useful tool in this institute as it allows optimum blood usage for surgeries. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 99-103 DOI: https://doi.org/10.22502/jlmc.v4i2.100